1999
DOI: 10.1063/1.124332
|View full text |Cite
|
Sign up to set email alerts
|

Depth and thermal stability of dry etch damage in GaN Schottky diodes

Abstract: GaN Schottky diodes were exposed to N2 or H2 Inductively Coupled Plasmas prior to deposition of the rectifying contact. Subsequent annealing, wet photochemical etching or (NH&S surface passivation treatments were examined for their effect on diode currentvoltage characteristics. We found that either annealing at 750 'C under N2, or removal of -500-600 A of the surface essentially restored the initial I-V characteristics. There was no measurable improvement in the plasma-exposed diode behavior with (NH&S treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 13 publications
3
68
0
Order By: Relevance
“…Inductively coupled plasma ͑ICP͒ etching of GaN led to severe degradations of the Schottky contact, the decrease of Schottky barrier height, and the increase of reverse leakage current by several orders of magnitudes. 4 Deep-level transient spectroscopy ͑DLTS͒ is an effective tool in obtaining information about traps in semiconductors. In particular, the depth distribution of deep levels is easily obtained, which is critical in interpreting the electrical properties of the devices.…”
Section: Observation Of Inductively Coupled-plasma-induced Damage On mentioning
confidence: 99%
“…Inductively coupled plasma ͑ICP͒ etching of GaN led to severe degradations of the Schottky contact, the decrease of Schottky barrier height, and the increase of reverse leakage current by several orders of magnitudes. 4 Deep-level transient spectroscopy ͑DLTS͒ is an effective tool in obtaining information about traps in semiconductors. In particular, the depth distribution of deep levels is easily obtained, which is critical in interpreting the electrical properties of the devices.…”
Section: Observation Of Inductively Coupled-plasma-induced Damage On mentioning
confidence: 99%
“…Figure 3(a) shows typical I-V characteristics of the Schottky diodes on the HDG sample. The diodes were leaky when the sample was etched at 100 W and 200 W of rf power due to the collective effects of etch-induced damage [11,12], while the NPT showed a decrease in leakage current for 100 W etched samples, especially in the reverse current region (not shown). This indicates that NPT treatment is an effective method for recovering the stoichiometry of the nitrogen deficient surface, consistent with the result of Figs.…”
Section: Resultsmentioning
confidence: 93%
“…The specific contact resistivity (ρ c ) and current-voltage (I-V) measurement, extracted from the ohmic contact and Schottky diodes, respectively, have been found to be very sensitive to surface damage induced by the dry-etching of semiconductors [8]. Although the effects of the ion bombardment of non-reactive gases in the plasma have been reported by exploiting a metal-semiconductor contact method [9][10][11][12], only a few results have been reported on the electrical characterization of dry-etched GaN under a actual device fabricating conditions. It is known that the depth of the damaged surface, etched with a chemical component, should be smaller than those etched using a physical component [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al have found that rapid thermal annealing of plasmaetched GaN recovers its electrical properties as demonstrated by the current-voltage characteristics of Schottky diodes. 12 High-temperature annealing might, however, lead to the preferential removal of N atoms from the GaN surfaces. Lee et al have reported that N 2 plasma treatment improves the photoluminescence (PL) characteristics of heavily damaged GaN surfaces.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%